Students' information behaviour and the role of academic library (Libellarium: journal for research in the field of information and related sciences, 2015)
In this paper the author presented the results of some of the available studies of students' information seeking behaviour conducted in different countries. The aim of these studies was to identify information needs, sources, and types of library use by the university students from various disciplinary fields. According to the results, the majority of the respondents needed the information for academic purposes (such as papers, assignments or examinations), frequently using information sources like books, journal articles, online sources etc. For many students the internet was a very important source in finding academic materials. Most of the students received advice in finding relevant information sources from their lecturers, peers, and librarians. This paper also describes some aspects related to information seeking behaviour of young students (Generation Y, and Millennial generation) who were influenced by their peers, and had poor understanding of their information needs. They prefer quick Google search, navigation through virtual libraries and spend more time downloading the materials than utilizing e-sources. Although the academic libraries were often used only for borrowing books and using reference material or printed periodicals, it has been established that the role of academic libraries was very significant in satisfying university students’ information needs. Further research that could be done building onto the selected studies is examination of information seeking behaviour of the students between different disciplines while taking into the account various context situations in which information tasks are performed. Moreover, further studies should explore factors that affect students’ library use, and identify significance of the library instruction in improving academic library services for users.
Keywords: information seeking behaviour; information needs; students; academic (university) libraries; information sources